Scrutinizing MBKM Programs; The Views of Experienced and Non-experienced English Students - Anggraini, Risa; Juliana, Juliana (Edumaspul: Jurnal Pendidikan, 2024)
Abstract A very significant policy in education has been introduced by the Indonesia Ministry of Education, Culture, Research and Technology, Nadiem Makarim, that is called as Merdeka Belajar Kampus Merdeka (MBKM). These programs offer many opportunities for those students to improve their self-development that can enhance their future career. Researchers use phenomenological study as a strategy of inquiry in this qualitative research method design. Four EFL students were being key informants in this research. They were students of English department from one state private university in Medan. Researchers used in-depth interview to gather the data information. Primarily, this research brings to a deep discussion on five major themes, they are 1) Challenges and practices, 2) Values of the program, 3) Impacts for the students, 4) Roles and responsibilities, and 5) Perspective changes. This research highlights the  thoughts on how to increase the evidentiary base for Kampus Merdeka’s future operationalization especially for the university’s policy on giving those students’ score on their course matters. Keywords: MBKM Programs, English students, Future Carreer Prospects. AbstrakKebijakan yang sangat signifikan dalam pendidikan telah diperkenalkan oleh Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Indonesia, Nadiem Makarim, yang disebut sebagai Merdeka Belajar Kampus Merdeka (MBKM). Program-program ini menawarkan banyak kesempatan bagi para siswa untuk meningkatkan pengembangan diri mereka yang dapat meningkatkan karir masa depan mereka. Peneliti menggunakan studi fenomenologi sebagai strategi penyelidikan dalam perancangan metode penelitian kualitatif ini. Empat siswa EFL menjadi informan kunci dalam penelitian ini. Mereka adalah mahasiswa jurusan Bahasa Inggris dari salah satu universitas swasta negeri di Medan. Peneliti menggunakan wawancara mendalam untuk mengumpulkan informasi data. Terutama, penelitian ini membawa diskusi mendalam tentang lima tema utama, yaitu 1) Tantangan dan praktik, 2) Nilai program, 3) Dampak bagi siswa, 4) Peran dan tanggung jawab, dan 5) Perubahan perspektif. Penelitian ini menyoroti pemikiran tentang bagaimana meningkatkan basis pembuktian untuk operasionalisasi Kampus Merdeka di masa depan, terutama untuk kebijakan universitas tentang memberikan nilai siswa tersebut pada materi kuliah mereka.Kata kunci: Program MBKM, mahasiswa bahasa Inggris, Prospek Karir Masa Depan.